Neural crest specification by Prohibitin1 depends on transcriptional regulation of prl3 and vangl1. Issue 10 (24th August 2015) - Deichmann, Christina; Link, Martina; Seyfang, Melanie; Knotz, Viktoria; Gradl, Dietmar; Wedlich, Doris
Summary A complex network of transcription factors regulates specification of neural crest cells at early neurula stage by stabilizing neural crest identity and activating neural crest effector genes so that distinct subpopulations evolve. In this network, c‐myc acts on top of the gene hierarchy controlling snail2, AP2 and prohibitin1 (phb1) expression. While snail2 and AP2 are well studied neural crest specifier genes little is known about the role of phb1 in this process. To identify phb1 regulated genes we analyzed the transcriptome of neural crest explants of phb1 morphant Xenopus embryos. Among 147 phb1 regulated genes we identified the membrane‐associated protein‐tyrosine phosphatase PRP4A3 (prl3) and the atypical cadherin and Wnt‐PCP component van gogh like1 (vangl1). Gain of function, loss of function and epistasis experiments allowed us to allocate both genes in the neural crest specification network between phb1 and twist. Interestingly, both, vangl1 and prl3 regulate only a small subset of neural crest marker genes. The identification of two membrane‐associated proteins as novel neural crest specifiers indicates that in addition to gene regulation by combinatory effects of transcription factors also post‐translational modifications (prl3) and cell–cell adhesion and/or regulation of cell‐polarity (vangl1) specify the identity of neural crest cell populations. genesis 53:627–639, 2015. © 2015 Wiley Periodicals, Inc.